(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. This study was designed to investigate the effect of N-acetylcysteine (NAC), as a potent and safe antioxidant, on inflammatory biomarkers of acute pyelonephritis in pediatric patients. Materials and Methods. Children (< 15 years old) admitted with a diagnosis of pyelonephritis were recruited in a randomized placebo-controlled trial. They were randomly allocated to 2 groups and recieved placebo or NAC effervescent tablets with daily dose based on their weight, for 5 days. The children were evaluated for serum procalcitonin level, leukocyte count, C-reactive protein (CRP), serum creatinine, and clinical symptoms on the 1st and the 5th days. Results. Seventy patients, 35 in each group, with a mean age of 5.54 ± 3.10 years completed the study. There was no significant difference between the two groups in the amount of changes in procalcitonin levels after 5 days (P = .90). Within-group analysis confirmed CRP reduction in both groups (P < .001); however, between-group analysis did not show significant difference in CRP reductions, either (P = .65). No significant differences were found between the two groups in the day of resolving pyuria (P = .46), day of resolving bacteriuria (P = .81), or reductions in leukocyte count (P = .64) and neutrophil count (P = .49). Conclusions. A short period of NAC administration with the recommended doses could not lead to a significant decrease in inflammation biomarkers. Studies on higher doses and longer duration of NAC administration along with evaluation of the long-term effects of the intervention by tools such as renal scntigraphy are suggested.